Characteristics of electroluminescent polythiophene derivatives containing electron transporting moiety - Choi, B; Lee, YM; Kim, DY; Lee, H (GORDON BREACH SCI PUBL LTD, 1999)
Spin-coated polymer LEDs were characterized by UV-Vis and fluorescence spectroscopies. Electrochemical properties of poly 3(2-(5-chlorobenzotriazolo) ethyl)thiophene LEDs as the emitting materials was studied by cyclic voltammetry. In cyclic voltammogram, PCBET shows reversible peaks at E(0)red = -2.1 V and E(0)ox= +0.91 V. Quantum efficiency of PCBET was much enhanced by introducing a benzotriazole moiety on the side chain.